A genomic‐augmented multivariate prognostic model for the survival of natural‐killer/T‐cell lymphoma patients from an international cohort. Issue 9 (5th July 2022) - Lim, Jing Quan; Huang, Dachuan; Chan, Jason Yongsheng; Laurensia, Yurike; Wong, Esther Kam Yin; Cheah, Daryl Ming Zhe; Chia, Burton Kuan Hui; Chuang, Wen‐Yu; Kuo, Ming‐Chung; Su, Yi‐Jiun; Cai, Qing‐qing; Feng, Yanfen; et al.
Abstract: With lowering costs of sequencing and genetic profiling techniques, genetic drivers can now be detected readily in tumors but current prognostic models for Natural‐killer/T cell lymphoma (NKTCL) have yet to fully leverage on them for prognosticating patients. Here, we used next‐generation sequencing to sequence 260 NKTCL tumors, and trained a genomic prognostic model (GPM) with the genomic mutations and survival data from this retrospective cohort of patients using LASSO Cox regression. The GPM is defined by the mutational status of 13 prognostic genes and is weakly correlated with the risk‐features in International Prognostic Index (IPI), Prognostic Index for Natural‐Killer cell lymphoma (PINK), and PINK‐Epstein–Barr virus (PINK‐E). Cox‐proportional hazard multivariate regression also showed that the new GPM is independent and significant for both progression‐free survival (PFS, HR: 3.73, 95% CI 2.07–6.73; p < .001) and overall survival (OS, HR: 5.23, 95% CI 2.57–10.65; p = .001) with known risk‐features of these indices. When we assign an additional risk‐score to samples, which are mutant for the GPM, the Harrell's C‐indices of GPM‐augmented IPI, PINK, and PINK‐E improved significantly ( p < .001, χ 2 test) for both PFS and OS. Thus, we report on how genomic mutational information could steer toward better prognostication of NKTCL patients.